Elucidation of the role of hexamine and other precursors in the formation of magnetite nanorods and their stoichiometry - Singh, Hema; Bhagwat, Shrikant; Jouen, Samuel; Lefez, Benoit; Athawale, Anjali A.; Hannoyer, Beatrice; Ogale, Satishchandra (Physical Chemistry Chemical Physics, 2010)
Hexamine is known to assist anisotropic growth of metal oxides and the same is also found to be true for magnetite nanosynthesis. In this work we elucidate the role of hexamine and other precursors in the formation of magnetite nanorods by the hydrothermal route and their stoichiometry. Various others hydrolyzing agents such as sodium hydroxide (NaOH), sodium hydroxide + hexamine, ammonia (NH(3)), ammonia + formaldehyde are also studied. The synthesized nanoparticles are characterized with the help of various techniques such as X-ray diffraction (XRD), FT-IR spectroscopy, UV-VIS-NIR spectroscopy, transmission electron microscopy (TEM), Mossbauer spectroscopy and SQUID magnetization measurements. It is found that only when ferric chloride, ferrous ammonium sulfate (FAS) and hexamine are used, well defined nanorods are formed. When sodium hydroxide and hexamine are used as a hydrolyzing system nearly spherical nanoparticles with small size (similar to 13 nm) are formed, as compared to the case of sodium hydroxide alone which leads to bigger cube like nanoparticles. Interestingly the decomposition products of hexamine do not lead to nanorod formation. Thus, slow decomposition of hexamine at elevated temperature and the consequent slow rise in pH is the key to the anisotropic growth of the iron oxide system.